Evolution mechanism of strain energy field and gravitational potential energy field of overlying rock under transient excitation of structure - Shenghu LUO; Jiabo GAO; Zhuangzhuang YAN; Yongping WU; Panshi XIE; Gang HAN; Hongwei WANG; Chengyang TIAN; Tong WANG; Mingming SUN (Meitan xuebao)
Revealing the aggregation and release mechanism of overlaying rock energy field is the theoretical basis for the prevention and cure of coal-rock dynamic disasters. By means of simulation experiment, numerical calculation and theoretical analysis, the mechanical models of two steady states before and after hard rock breaking were established. The step change characteristics of coal and rock under load before and after structural transient were compared and analyzed. The evolution mechanism of strain energy and gravitational potential energy accumulation and release of overlying rock under structural transient excitation was studied. The results show that it is affected by self-weight stress field and mining unloading effect, the rock strata within the mining influence range interact and restrict each other, and there is a close and complex mechanical connection. The structural transient induced by hard rock breaking, it breaks the balance of the original old order between the rock strata. It leads to the transient change of the mechanical relation between the strata and the load transfer path of the overlying strata. The strain energy field and the gravitational potential energy field of the overlying strata change accordingly. In addition, the transient change of overburden load transfer path will cause different instantaneous loading and unloading of coal and rock in different areas of stope space, resulting in differences in the energy evolution characteristics of overlying strata in different regions. Among them, after the fracture of the lower hard rock stratum, the instantaneous unloading of the internal force of the fracture surface and the instantaneous loading formed by the transient transition of the load transfer path of the overlying rock make some areas near the goaf instantaneously rebound upward and release strain energy, the instantaneous subsidence and release of gravitational potential energy in some areas within the rebound zone. At the same time, the instantaneous unloading of the support load in the transient region of the structure makes the upper hard rock layer sink instantaneously and the deformation increase sharply, and the gravitational potential energy is released and the strain energy is accumulated. In essence, the dynamic mechanical response process of coal rock in mining field under transient excitation of structural is a dynamic process of the evolution of the original space-time structure of coal rock in mining field to the new space-time structure after the original space-time structure of coal rock in mining field is broken. There is a mutual conversion of strain energy, gravitational potential energy and kinetic energy, accompanied by the aggregation and release of strain energy and gravitational potential energy. On the whole, the release area of overlaying rock strain energy is small, mainly concentrated in the instantaneous unloading area, and the rest areas increase instantaneously. The release range of gravitational potential energy is large, and only the rebound area of the lower hard rock layer increases slightly.